2017
DOI: 10.1108/apjml-07-2016-0135
|View full text |Cite
|
Sign up to set email alerts
|

The effects of consumer perception of volume discount benefits on intention to purchase grocery products

Abstract: Purpose The purpose of this paper is to investigate the effects of consumers’ perceptions towards volume discount (VD) benefits on their intention to purchase grocery products under this scheme using deal proneness as a moderator. Design/methodology/approach Data were gathered through a survey of 583 Malaysian consumers, and were analysed using the partial least squares technique. Findings The results showed that perceived savings, self-expression value, and convenience positively affected consumers’ inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 103 publications
0
25
0
1
Order By: Relevance
“…The population of this study consisted of all Malaysian people living in Kuala Lumpur, Penang, Johor and Sabah who have a driving licence and a car. According to Iranmanesh et al [58], these four states are sufficiently representative of the entire Malaysian population. Data collection was carried out by giving a hard copy of the questionnaire to 450 respondents.…”
Section: Data Collection and The Samplementioning
confidence: 99%
“…The population of this study consisted of all Malaysian people living in Kuala Lumpur, Penang, Johor and Sabah who have a driving licence and a car. According to Iranmanesh et al [58], these four states are sufficiently representative of the entire Malaysian population. Data collection was carried out by giving a hard copy of the questionnaire to 450 respondents.…”
Section: Data Collection and The Samplementioning
confidence: 99%
“…With a sample size of 860 respondents on the topic relating to the factors involving in the selection of stores for the urban grocery buying journey as regards over than 150 stores in US including various variables, showed that consumers are expected to shop in stores that may provide large products in the store and less expensive. For example, when there are rises of about 20% and 15% in a point of view of convenience of loppy discount department stores and supermarkets in shopping plazas, respectively, it can be expected a 10% increment to counterbalance in the trip times to these stores (Iranmanesh, Jayaraman, Zailani, & Ghadiri, 2017). According to the Journal of Public Administration and Governance, the relationship between price discount and consumer behavior has been shown and it's has been seen a much positive correlation between price reduction and the buying behavior with a signi icance value less than 0.05.…”
Section: Pricementioning
confidence: 99%
“…Bhasin (2018) argued that many sales promotion can stimulate the consumer to shop in the store nevertheless coupons are the primordial tools to be used whether you would like to see the customer come back to repurchase in the store (Ashraf et al, 2014). Abundant studies have tackled the case of sales promotion that best impacting the business and simultaneously increasing the pro it and then according to (Ghifari & Saefulloh, 2018), one of the best sales promotion technique to use by marketers to achieve their businesses goals especially in business to consumer (B to C) level is coupons (Iranmanesh et al, 2017).…”
Section: Couponmentioning
confidence: 99%
“…Гастрономическая сфера привлекает сегодня исследователей широкого круга в основном из-за революционных изменений технологий производства продуктов питания, принципов их реализации и, конечно же, потребления [16][17][18].…”
Section: основные направления революции питания 40unclassified